2019
DOI: 10.1111/bjc.12221
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of severe life events, attachment style, and depression – Using a new online approach

Abstract: Objectives. Severe life events are established as provoking agents for depression in combination with vulnerability factors. Identifying features of severe events improves the prediction of disorder but are rarely utilized, mainly because life event research is increasingly dominated by self-report checklists with no capacity for inferring such characteristics. This paper investigates the association of severe life events' features with depression and insecure attachment styles using a new online measure of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
0
7
0
1
Order By: Relevance
“…A new online approach – Computerised Life Events Assessment Record CLEAR – mimics aspects of the interview ratings with good reliability and validity and is able to provide ratings of the threat as well as the further characteristics in a large number of event categories (Bifulco et al ., 2019). The overlap of trauma and other severe events and their characteristics have been investigated with some success in relation to depression (Bifulco et al ., under review). Whilst these scores constitute reported rather than investigator-coded characteristics of events, aids to rating online through written and video instruction, and detailed labelling of rating points with examples potentially objectifies ratings.…”
Section: Testing Overlap Of Markedly Severe Events Their Attributes mentioning
confidence: 99%
“…A new online approach – Computerised Life Events Assessment Record CLEAR – mimics aspects of the interview ratings with good reliability and validity and is able to provide ratings of the threat as well as the further characteristics in a large number of event categories (Bifulco et al ., 2019). The overlap of trauma and other severe events and their characteristics have been investigated with some success in relation to depression (Bifulco et al ., under review). Whilst these scores constitute reported rather than investigator-coded characteristics of events, aids to rating online through written and video instruction, and detailed labelling of rating points with examples potentially objectifies ratings.…”
Section: Testing Overlap Of Markedly Severe Events Their Attributes mentioning
confidence: 99%
“…Se entiende por evento vital negativo cualquier experiencia personal percibida por la como altamente amenazante o perjudicial, de manera que le demanda un reajuste sustancial de su vida y comportamiento. Algunos ejemplos de éstos serían la muerte de alguien cercano, la ruptura de cualquier relación significativa, o la pérdida de un empleo , es decir, se refiere a la percepción de una pérdida como importante por sus implicaciones a nivel emocional, cognitivo y/o conductual (Jin, Sun, & Wang, 2018;Zou et al 2018), lo cual puede ser agravado cuando se tiene un estilo de apego inseguro (Bifulco, Kagan, & Spence, 2019).…”
Section: Modelo De Solución De Problemas De La Depresiónunclassified
“…One crucial limitation is that we did not assess attachment styles in any of our samples, although our results can be interpreted to draw some preliminary conclusions and inspire future research. First of all, previous results show the relationship between a disorganized attachment and a higher probability of suffering anxiety (86), depression (87), addiction (88), or PTSD (89), and expressing personality disorders such as borderline, avoidant, or antisocial, among others (90). In turn, recent research has shown an association between insecure attachment, alcohol/substance addiction, and an increased amount of borderline personality organization (57).…”
Section: Discussionmentioning
confidence: 96%